Investigation on Water Consumption Pattern in Traditional Malaysian Kampung: An Insight Study on Water and Environmental Issues - Ahmad Adzlan, Fadzli Khairi; M. I., Shahidul; Syed Tarmizi, Syed Shazali; Abdullah, Yassin; Mohd. Azrin, Mohd Said; Hishammudin, Afifi Huspi; C. H., Ting (ENCON 2013, 2013)
This research aims to investigate on water consumption pattern of traditional Malaysian kampung. Random sampling survey method was adapted to capture information on water consumption from the relevant stakeholders. The water consumption pattern is divided into five major categories such as cooking, drinking, washing, gardening and others. Study indicates that water consumption for a family of four persons is about 140 l/day, which is below average in Malaysian standard. Water consumption for cooking, drinking, washing, gardening and others found to be 7, 15, 8, 2.5, and 3 litres respectively. The findings benefit government agencies in developing strategy to supply clean water to the kampung people. The study suggests further in-depth study on the essentially important topics in order to generate robust information for developing a general model to be used for government policies.